Occupational Fatigue: Relationship With Personality Traits and Decent Work - Di Fabio, Annamaria; Svicher, Andrea; Gori, Alessio (Frontiers in Psychology, 2021)
Psychology of working theory (PWT) and psychology of working framework (PWF) offered a psychological view of decent work. The present study examined the associations among personality traits, decent work and Occupational Fatigue Exhaustion Recovery Scale (OFER). Two hundred and thirty four participants filled out the Big Five Questionnaire, the Italian version of the Decent Work Scale, and the Italian version of the OFER Scale. Hierarchical regressions showed that decent work explained incremental variance beyond personality traits with respect to OFER both considering total score and its three dimensions (chronic fatigue, acute fatigue, persistent fatigue). The present study underlined the value of decent work in relation to occupational fatigue beyond the contributions of personality, in particular in relation to the dimensions of Adequate compensation and Free time and rest for less occupational fatigue (both as total and as dimensions).